SELECTIVE DEPTH ANALYSES OF THE ALTERATION PRODUCTS OF BORNITE, CHALCOPYRITE AND PYRITE PERFORMED BY XPS, AES, RBS - Pratesi G.; Cipriani C. (My University, 2000)
The comparative application of three complementary surface analytical techniques allows us to investigate the alteration process and to probe selectively, as a function of depth, the oxidation products of bornite, chalcopyrite and pyrite. Starting from a pristine surface, the samples have been studied at different stages of alteration up to a strongly oxidized state after two years of air exposure. In spite of their different compositions, some similarities exist in their oxidation: iron sulfates seem to be mainly responsible for the increase of alteration whereas copper sulfide layers, due to iron depletion from the subsurface area, act as a barrier to the progress of alteration.